Invasive Seaweed Rugulopteryx okamurae: A Potential Source of Bioactive Compounds with Antioxidant Activity - Radia N. A. Belhadj; Cristina Mellinas; Alfonso Jiménez; César Bordehore; Maria Carmen Garrigós (MDPI AG, 2024)
Rugulopteryx okamurae (RO) is a species of brown seaweed that has invaded several shorelines worldwide, including the Spanish Mediterranean and the Strait of Gibraltar coasts, causing serious environmental and economic problems. This work aimed to characterize the bioactive composition of RO. A high content of carbohydrates (58.7 ± 2.6 wt%), fats (17.1 ± 0.4 wt%), and ashes (14.3 ± 0.2 wt%) were found, together with lower protein content (5.5 ± 1.8 wt%). Holocellulose was the most abundant polysaccharide fraction (49.2 ± 1.3 wt%), showing 43.4 ± 2.0 wt% of cellulose and 5.8 ± 0.7 wt% of hemicellulose, followed by lignin (18.9 ± 2.5 wt%). The monosaccharides composition showed a high level of glucose (13.2 ± 1 wt%) and glucuronic acid (9.3 ± 0.5 wt%). RO contained high levels of essential nutrients (Ca, K, Na, S, Mg), trace minerals (Mn, Mo, Se, and Cu), and some toxic heavy metals (Ni, Cd, As). The main fatty acid present in RO was palmitic acid (C16:0, 30.8 ± 3.0 mg/100 g), followed by myristic acid (C14:0, 19.3 ± 2.4 mg/100 g) and eicosatetraenoic acid (C20:4, 19.2 ± 1.3 mg/100 g). The extract obtained by microwave-assisted extraction (MAE) presented significant contents of polyphenols (2.7 ± 0.2 mg GAE/g) and antioxidant activity (3.0 ± 0.4 mg TE/g DPPH, 4.5 ± 0.3 mg TE/g ABTS, 4.7 ± 0.3 mg TE/g FRAP). Six main polyphenols were identified by HPLC-MS/MS, showing higher contents of gallic acid (20.7 ± 1.5 mg/g) and chlorogenic acid (9.7 ± 0.5 mg/g). These results highlight the possibilities offered in the valorization of RO to obtain bioactive compounds with antioxidant performance in several applications.